New Approach for Calculate Exponential Integral Function - Tawfiq, L. N. M.; Khamas, A. H. (Iraqi Journal of Science, 2023)
This manuscript presents a new approach to accurately calculating exponential integral function that arises in many applications such as contamination, groundwater flow, hydrological problems and mathematical physics. The calculation is obtained with easily computed components without any restrictive assumptions A detailed comparison of the execution times is performed. The calculated results by the suggested approach are better and faster accuracy convergence than those calculated by other methods. Error analysis of the calculations is studied using the absolute error and high convergence is achieved. The suggested approach out-performs all previous methods used to calculate this function and this decision is based on the getting results.